2007
DOI: 10.1371/journal.ppat.0030136
|View full text |Cite
|
Sign up to set email alerts
|

Members of a Large Retroposon Family Are Determinants of Post-Transcriptional Gene Expression in Leishmania

Abstract: Trypanosomatids are unicellular protists that include the human pathogens Leishmania spp. (leishmaniasis), Trypanosoma brucei (sleeping sickness), and Trypanosoma cruzi (Chagas disease). Analysis of their recently completed genomes confirmed the presence of non–long-terminal repeat retrotransposons, also called retroposons. Using the 79-bp signature sequence common to all trypanosomatid retroposons as bait, we identified in the Leishmania major genome two new large families of small elements—LmSIDER1 (785 copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
149
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(159 citation statements)
references
References 72 publications
8
149
0
2
Order By: Relevance
“…Bringaud et al (41) found evidence of accumulation of fragments from a now inactive family of retrotransposons in the UTRs of some predicted mRNAs, and further found that these genes showed lower than average mRNA levels. The pattern is suggestive of a possible evolution of a regulatory function.…”
Section: Types Of Sges and Their Consequencesmentioning
confidence: 99%
“…Bringaud et al (41) found evidence of accumulation of fragments from a now inactive family of retrotransposons in the UTRs of some predicted mRNAs, and further found that these genes showed lower than average mRNA levels. The pattern is suggestive of a possible evolution of a regulatory function.…”
Section: Types Of Sges and Their Consequencesmentioning
confidence: 99%
“…Quite useful for gene function studies are the reporter genes, e.g. luciferase or GFP (green fluorescent protein), which are applicable to studying regulatory elements involved in mRNA stability or initiation of translation control [89][90][91] and to evaluate protein interactions or subcellular distribution.…”
Section: Forward and Reverse Geneticsmentioning
confidence: 99%
“…In addition, gene expression has been shown to change dramatically throughout the complex life cycles of these parasites (Haile and Papadopoulou 2007;Rochette et al 2008;Nilsson et al 2010;Siegel et al 2010). Regulation of mRNA decay rates through interactions of RNA-binding proteins (RBPs) with cis-acting sequences in 3 ′ UTRs of trypanosomatid transcripts is central in determining the fate of mRNAs and thus fine-tuning developmental gene expression (McNicoll et al 2005;Bringaud et al 2007;Haile and Papadopoulou 2007;Haile et al 2008;Müller et al 2010b;Kramer 2012;Clayton 2013). Several RBPs, such as zinc finger proteins, Alba-domain proteins, and Pumilio (PUF) proteins, have been found to regulate mRNA stability in trypanosomatids (Clayton 2013;Dupé et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Leishmania, we have previously identified a large family of extinct retroposon elements termed short interspersed degenerate retroposons (SIDERs) (>2000 copies per genome), predominantly located within 3 ′ UTRs (Bringaud et al 2007(Bringaud et al , 2008Smith et al 2009). Members of the two major SIDER subfamilies were shown to regulate mRNA turnover in a stage-and species-specific manner (SIDER2 subfamily) (Bringaud et al 2007;Rochette et al 2008;Müller and Papadopoulou 2010;Müller et al 2010a,b) or mRNA translation (SIDER1 subfamily) (Boucher et al 2002;McNicoll et al 2005), and possibly to form RNA regulons (Ouellette and Papadopoulou 2009;Smith et al 2009).…”
Section: Introductionmentioning
confidence: 99%